Cost analysis of the treatment of severe acute malnutrition in West Africa - Isanaka, Sheila (Matern Child Nutr, 2016)
We present an updated cost analysis to provide new estimates of the cost of providing community‐based treatment for severe acute malnutrition, including expenditure shares for major cost categories. We calculated total and per child costs from a provider perspective. We categorized costs into three main activities (outpatient treatment, inpatient treatment, and management/administration) and four cost categories within each activity (personnel; therapeutic food; medical supplies; and infrastructure and logistical support). For each category, total costs were calculated by multiplying input quantities expended in the Médecins Sans Frontières nutrition program in Niger during a 12‐month study period by 2015 input prices. All children received outpatient treatment, with 43% also receiving inpatient treatment. In this large, well‐established program, the average cost per child treated was €148.86, with outpatient and inpatient treatment costs of €75.50 and €134.57 per child, respectively. Therapeutic food (44%, €32.98 per child) and personnel (35%, €26.70 per child) dominated outpatient costs, while personnel (56%, €75.47 per child) dominated in the cost of inpatient care. Sensitivity analyses suggested lowering prices of medical treatments, and therapeutic food had limited effect on total costs per child, while increasing program size and decreasing use of expatriate staff support reduced total costs per child substantially. Updated estimates of severe acute malnutrition treatment cost are substantially lower than previously published values, and important cost savings may be possible with increases in coverage/program size and integration into national health programs. These updated estimates can be used to suggest approaches to improve efficiency and inform national‐level resource allocation.